2021
DOI: 10.1055/a-1364-4160
|View full text |Cite
|
Sign up to set email alerts
|

A novel endoscopic purse-string suture technique, “loop 9”, for gastrointestinal defect closure: a pilot study

Abstract: Background and study aims: This study aimed to assess the feasibility and efficacy of the novel loop 9 method of gastrointestinal (GI) defect closure. Patients and methods: Twenty patients underwent a GI procedure that required defect closure. Loop 9 can be delivered through a single instrument channel (3.2 mm) and released at the defect site. After being anchored by two clips positioned at the opposite sides of the defect edge, loop 9 was tightened by pulling the end of the suture intraluminally using biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Recently, Inoue et al. reported a novel endoscopic purse‐string suture technique, “loop 9”, for gastrointestinal defect closure, and it took 14 min to complete the procedure 21 . This method and ours are similar in the sense that the knot in the loop is pushed with the outer sheath and slides to tighten the loop, but there are some differences in the shape of the device and its usage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, Inoue et al. reported a novel endoscopic purse‐string suture technique, “loop 9”, for gastrointestinal defect closure, and it took 14 min to complete the procedure 21 . This method and ours are similar in the sense that the knot in the loop is pushed with the outer sheath and slides to tighten the loop, but there are some differences in the shape of the device and its usage.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Inoue et al reported a novel endoscopic purse-string suture technique, "loop 9", for gastrointestinal defect closure, and it took 14 min to complete the procedure. 21 This method and ours are similar in the sense that the knot in the loop is pushed with the outer sheath and slides to tighten the loop, but there are some differences in the shape of the device and its usage. While the loop 9 technique has already been shown to be feasible and effective in a small number of actual patients, FLEXLOOP has not yet been used in a clinical setting and is currently being tested for preclinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a recently released study conducted by Pang et al ., 28 1.12% and 0.04% of patients encountered delayed bleeding and perforation in the endoscopic group with gastric GISTs (≤ 5 cm); however, no postoperative hemorrhage or perforation happened in the surgical group ( n = 141). With the development of endoscopic techniques, endoscopic suture techniques have made great progress in recent years 31,32 . The incidence of delayed bleeding and perforation became low, and they were all managed timely and successfully, suggesting postoperative monitoring and early detection of potential adverse events were of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Their successful application is however being undermined by a number of pitfalls, both procedure-related (e. g. respiratory fluctuations, poor endoloop device maneuverability when kept outside the endoscope) and instrument-related (e. g. difficulty grasping the tail or stem of the endoloop, resulting from the hooked shape of the device) 3 . Herein, we illustrate a modification of the endoloop and endoclips technique, inspired by the “loop 9” method 4 , that can be applied as a less cumbersome yet effective alternative to similar procedures.…”
Section: Endoscopy E-videosmentioning
confidence: 99%